Women’s perspectives on termination service delivery in Vietnam: a cross-sectional survey in three provinces - Ngo TD; Free C; Le HT; Edwards P; Pham KH; Nguyen YB; Nguyen TH (Dove Medical Press, 2014)
Thoai D Ngo,1,2 Caroline Free,1 Hoan T Le,3 Phil Edwards,1 Kiet HT Pham,4 Yen BT Nguyen,4 Thang H Nguyen5 1Faculty of Epidemiology and Population Health, London School of Hygiene and Tropical Medicine, 2Research, Monitoring, and Evaluation Team, Health System Department, Marie Stopes International, London, UK; 3Department of Environmental Health, Hanoi Medical University, 4Department of Health Economics, Hanoi Medical University, 5Research and Metrics Team, Marie Stopes International Vietnam, Hanoi, Vietnam Objective: To explore the perspectives of abortion service users regarding termination methods and abortion service delivery in Vietnam. Materials and methods: Structured exit interviews were conducted between August and November 2011 with women who underwent termination of pregnancy at 62 public health facilities in Hanoi, Khanh Hoa, and Ho Chi Minh City in Vietnam. All women presenting for termination during the study period were recruited to participate in the study. Following their abortion, women were asked about their perspectives on abortion service delivery and attributes of medical abortion (MA) versus manual vacuum aspiration (MVA). Multiple logistic regression was used to assess the association between current method uptake and each attribute. Results: A total of 1,233 women were included in the survey: 541 (43.9%) from Hanoi, 163 (13.2%) from Khanh Hoa, and 529 (42.9%) from Ho Chi Minh: 23.1% underwent MA; 78.9% reported that women should be given a choice between MA and MVA; and 77.6% thought that abortion services were accessible. Among the 48% who responded, 30.1% thought that MA should be made available at primary/secondary health care facilities. Among women who had previously undergone both methods, women who reported that MA "feels more natural" (like a menstrual regulation/period) were more likely to choose MA for their current abortion (odds ratio 2.15, 95% confidence interval 1.26–3.69). Conclusion: MA uptake is significantly lower than MVA uptake. Further insights to women's perceptions of MA in Vietnam could help improve abortion service delivery in the country. Keywords: Vietnam, medical abortion, misoprostol, mifepristone, manual vacuum aspiration, health service delivery